The study of personal factors of adolescents affecting their attitudes towards the success and failure of the other - Alexandra Serdakova; Natalia Shustikova; Nikita Kishkin; Marina Asafaylo; Nikolay Kravtsov (International Journal of Evaluation and Research in Education (IJERE), 2023)
The purpose of the research was to study personal factors that can influence the formation of attitudes towards the success and failure of the other in adolescence. The psychodiagnostics techniques used in the study included Beskova’s methodology modified by Dubovskaya and Serdakova, the methodology for diagnosing the level of empathy by Boyko, emotional intelligence test by Hall and Dembo-Rubinstein self-esteem measurement methodology modified by Prikhozhan. There is a correlation between the attitudes towards the success and failure of a peer and personality traits in adolescence. It has been shown that young men and women are frequently characterized by a positive perception of the other, sincere joy and admiration for their success, and sympathy in case of failure and success of the other. A direct correlation was revealed between the level of empathy and a positive attitude towards the success of the other, which confirms the role of the personal factor in the formation of interpersonal relations.